Modularity, Redundancy and the Problem of “Sex” - Nucleares, C Centro de Ciencias de la Complejidad and Instituto de Ciencias; México, Universidad Nacional Autónoma de; México, (Discontinuity, Nonlinearity, and Complexity, 2026)
Homologous recombination, and the associated notion of sexual reproduction, are ubiquitous in the evolution of biological organisms. However, there is still no clear, generally accepted understanding of why it exists and under what circumstances it is useful. Here, we argue that its utility is strongly linked to specific types of fitness landscape. In particular, landscapes that are quasi-modular (weak additive epistasis) or redundant (negative epistasis), two properties that are also ubiquitous in biological systems. We further argue that recombination and modularity together are responsible for the formation of “building block hierarchies” where, to make compatible the two different types of building block, landscape blocks associated with modular fitness landscapes and uilding Block schemata defined by the recombination distribution, a meta-evolution is necessary, wherein the recombination distribution itself evolves, leading to recombination hotspots at the boundaries of landscape blocks. We finally argue that recombinative dynamics and modular landscapes are necessary conditions for the formation of building block hierarchies and, ultimately, life itself.